2021
DOI: 10.1021/acsami.1c14947
|View full text |Cite
|
Sign up to set email alerts
|

Manipulating Uniform Nucleation to Achieve Dendrite-Free Zn Anodes for Aqueous Zn-Ion Batteries

Abstract: The essence of Zn dendrite formation is ultimately derived from Zn nucleation and growth during the repeated Zn plating/stripping process. Here, the nucleation process of Zn has been analyzed using ex situ scanning electron microscopy to explore the formation of the initial Zn dendrite, demonstrating that the formation of tiny protrusions (the initial state of Zn dendrites) is caused by the inhomogeneity of Zn nucleation. Based on this, the uniform Zn nucleation is promoted by the Ni5Zn21 alloy coating (ZnNi) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 58 publications
(93 reference statements)
0
40
0
Order By: Relevance
“…Cyclic stability of Zn anodes. Voltage profiles of bare Zn and Zn@TPZA anodes at a) 5 mA cm –2 /5 mAh cm –2 and b) 10 mA cm –2 /10 mAh cm –2 ; SEM images of c) bare Zn and d) Zn@TPZA with TPZA layer peeled off after cycling; CE of the two anodes at e) 5 mA cm –2 /5 mAh cm –2 and f) 10 mA cm –2 /10 mAh cm –2 ; g) Comparison of cumulative capacity and cycling capacity of Zn@TPZA and other reported Zn anodes with various coating layers (Kaolin, [ 29 ] indium, [ 12 ] PDMS/TiO 2 , [ 16 ] MOF, [ 30 ] polyamide, [ 31 ] ZnS, [ 32 ] ZnO, [ 33 ] poly(vinyl butyral), [ 34 ] polyimide, [ 35 ] ZnSe, [ 5 ] PAN‐Si 3 N 4 , [ 15 ] PVDF/TiO 2 , [ 17 ] BiTiO 3 , [ 36 ] NaTi 2 (PO 4 ) 3 , [ 37 ] Ga‐In‐Zn, [ 38 ] ZnNi, [ 39 ] PDA, [ 40 ] Poly‐ZnP 2 O 6 /ZnF 2 [ 26 ] ).…”
Section: Resultsmentioning
confidence: 99%
“…Cyclic stability of Zn anodes. Voltage profiles of bare Zn and Zn@TPZA anodes at a) 5 mA cm –2 /5 mAh cm –2 and b) 10 mA cm –2 /10 mAh cm –2 ; SEM images of c) bare Zn and d) Zn@TPZA with TPZA layer peeled off after cycling; CE of the two anodes at e) 5 mA cm –2 /5 mAh cm –2 and f) 10 mA cm –2 /10 mAh cm –2 ; g) Comparison of cumulative capacity and cycling capacity of Zn@TPZA and other reported Zn anodes with various coating layers (Kaolin, [ 29 ] indium, [ 12 ] PDMS/TiO 2 , [ 16 ] MOF, [ 30 ] polyamide, [ 31 ] ZnS, [ 32 ] ZnO, [ 33 ] poly(vinyl butyral), [ 34 ] polyimide, [ 35 ] ZnSe, [ 5 ] PAN‐Si 3 N 4 , [ 15 ] PVDF/TiO 2 , [ 17 ] BiTiO 3 , [ 36 ] NaTi 2 (PO 4 ) 3 , [ 37 ] Ga‐In‐Zn, [ 38 ] ZnNi, [ 39 ] PDA, [ 40 ] Poly‐ZnP 2 O 6 /ZnF 2 [ 26 ] ).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is of great significance to characterize the diffusion properties of materials to ions through theoretical calculation. 68…”
Section: Discussionmentioning
confidence: 99%
“…The diffusion of ions is also very meaningful for zinc ions batteries and all kinds of new battery systems because it is the control step of dynamics. Therefore, it is of great significance to characterize the diffusion properties of materials to ions through theoretical calculation 68 …”
Section: Discussionmentioning
confidence: 99%
“…[33][34][35] On the other hand, it is found that during the long-term charge/discharge process, O 2 in the electrolyte will react with metal state zinc to form zinc-based oxide byproducts which would cause the passivation of the zinc anode and negatively affect the battery performance. [28,36] More recently, binary Zn alloys such as Zn-Al, [37] Zn-Ag, [29,30] and Zn-Ni [38] alloys have been probed to protect Zn anode from dendrite growth and side reactions. Compared with pure Zn, these alloys have distinct features, like higher ionic conductivity, lower surface energy, better wettability, and higher resistance to the presence of oxygen.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, binary Zn alloys such as Zn–Al, [ 37 ] Zn–Ag, [ 29,30 ] and Zn–Ni [ 38 ] alloys have been probed to protect Zn anode from dendrite growth and side reactions. Compared with pure Zn, these alloys have distinct features, like higher ionic conductivity, lower surface energy, better wettability, and higher resistance to the presence of oxygen.…”
Section: Introductionmentioning
confidence: 99%